2020
DOI: 10.1051/e3sconf/202019505008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the soil type on the biocementation process by enzymatic way

Abstract: The effect of the enzymatic CaCO3 precipitation on the behaviour of four soils (from a poorly graded sand to a fine and organic soil) is studied in this work. The analysis is based on the results of UCS tests, where the results from the non-stabilised specimens are compared with specimens stabilised with a urease concentration of 8 kU/L and an equimolar solution of urea-CaCl2 of 0.5 mol/L. Additionally, pH and scanning electron microscopy (SEM) tests with energy dispersive X-ray (EDX) analyses are performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The increased brittleness of the treated soil samples was also consistent with the typical stress-strain behaviour of soils stabilised with conventional chemical stabilisers such as cement or lime. However, in other studies of the group [21,28], the enzymatic treatment of a natural fine-grained organic soil of an organic matter content of 11% did not have a positive effect on the strength. A reason put forward for this was that SEM analysis showed that the organic matter was coating the mineral soil particles, thus potentially hindering the formation of bonds between the soil particles and the CaCO 3 crystals.…”
Section: Introductionmentioning
confidence: 65%
“…The increased brittleness of the treated soil samples was also consistent with the typical stress-strain behaviour of soils stabilised with conventional chemical stabilisers such as cement or lime. However, in other studies of the group [21,28], the enzymatic treatment of a natural fine-grained organic soil of an organic matter content of 11% did not have a positive effect on the strength. A reason put forward for this was that SEM analysis showed that the organic matter was coating the mineral soil particles, thus potentially hindering the formation of bonds between the soil particles and the CaCO 3 crystals.…”
Section: Introductionmentioning
confidence: 65%